Santa cruise [large type] - Michaels, Fern (Wheeler Publishing, a part of Gale, a Cengage Company, 2021)
"At Ridgewood High, Amy, Frankie, Rachael and Nina formed a deep bond. Now they're back for a reunion. Nina moved to Hollywood and landed a recurring role on a sitcom. Amy is now a Silicon Valley bioengineer. Frankie works for a New York publishing house. Rachael married--mostly to please her parents--but is now divorced. In late December, Amy, Rachael, Frankie and Nina gather in Miami, ready to board their state-of-the-art cruise ship. The highlight of the week will be a magnificent New Year's Eve celebration. Holidays don't always go as planned, but over the course of one festive, unforgettable week, all four will set sail on surprising new adventures"--